Optymalny podział inwestycji między dwa sektory — wyniki badań empirycznych - Panek, Emil (Wydział Prawa i Administracji UAM, 1987)
The paper is composed of two parts. In the first, theoretical one, the author presents the Leontief dynamic model and investigates the variants of the solution of the problem of optimum distribution of investment between sectors in the two-sector version of that model. The solution is obtained by means of the Pontriagin maximum principle. In the second, empirical part, the author presents the results of calculations made on the basis of statistical data concerning Poland in the years 1965 - 1975. The author critically evaluates economically unrealistic variants of solution which postulat sudden "switches" in the distribution of investment between sectors. In the author's opinion, fully realistic processes taking place in real economies are characterized by "smooth" trajectories of investments and consumption. He shows that if the rules of investments distribution between sectors resulting from that solution had been applied in years 1965 -1975, a higher level of production of means of production and similar level of production of consumption goods would have been achieved. The author indicates that in view of the above solutions the leading plans of socio-economic development formulated on the highest level of authority should cover longer periods than the five-year-ones.
The optimum distribution of investments between two sectors — the results of simple empirical studies